The immunohistochemical landscape of the VEGF family and its receptors in glioblastomas - Luiz Victor Maia Loureiro (Surgical and Experimental Pathology, 2020)
Abstract Background Angiogenesis is one of the hallmarks of cancer. This complex mechanism of tumor progression provides tumors cells with essential nutrients. There have been a limited number of investigations of markers of angiogenesis in Glioblastomas (GBMs), and most previous studies have focused on VEGF-A. Recent evidence suggests that there is a complex lymphatic system in central nervous system (CNS), which suggests VEGF-C and VEGF–D as interesting biomarker candidates. This study was designed to evaluate the expressions of VEGF-A, −C, −D and their co-receptors, VEGFR-1, VEGFR-2, and VEGFR-3 by immunohistochemistry (IHC) using a series of GBMs. In addition, we evaluate any putative correlations between IHC expression levels of VEGF and clinical data of patients. Methods Tumor samples of 70 GBM patients (64 isocitrate dehydrogenase-1 wildtype (wtIDH-1) and 6 mutant (mutIDH-1)) were assessed by IHC using tissue microarray platforms for VEGF subunits and their co-receptors. The medical records were reviewed for clinical and therapeutic data. Results All VEGF subunits and receptors were highly expressed in GBMs: 57 out of 62 (91.9%), 53 out of 56 (94.6%) and 55 out of 63 cases (87.3%) showed VEGF-A, VEGF-C and -D imunoexpression, respectively. Interestingly, we had found both nuclear and cytoplasmic localization of VEGF-C staining in GBM tumor cells. The frequency of immunoexpression of VEGF receptors was the following: VEGFR-1, 65 out of 66 cases (98.5%); VEGFR-2, 63 out of 64 cases (98.4%); VEGFR-3, 49 out of 50 cases (90.0%). There were no significant differences in the patient overall survival (OS) related to the VEGF staining. A weak and monotonous correlation was observed between VEGF and its cognate receptors. The pattern of VEGF IHC was found to be similar when GBM mutIDH-1 subtypes were compared to wtIDH-1. Conclusion Both VEGF-C and –D, together with their receptors, were found to be overexpressed in the majority GBMs, and the IHC expression levels did not correlate with OS or IDH status. To understand the significance of the interactions and increased expression of VEGF-C, VEGF-D, VEGFR-2, and VEGFR-3 axis in GBM requires more extensive studies. Also, functional assays using a larger series of GBM is also necessary to better address the biological meaning of nuclear VEGF-C expression in tumor cells.